PROSPECTS FOR IMPROVING THE TRAINING OF MILITARY SPECIALISTS IN UZBEKISTAN - Khujaev Botir Tavakkalovich (Galaxy International Interdisciplinary Research Journal, 2023)
After the independence of our country, the attention to the military field increased even more. The opportunity created by our president has led to great opportunities. This article talks about opportunities and created conditions and prospects in the military field.